2019
DOI: 10.1177/2050640618818942
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of endoscopic ultrasound in gastric adenocarcinoma patient selection for neoadjuvant therapy

Abstract: Background: Recent studies demonstrated the positive impact of neoadjuvant treatment in locally advanced gastric cancer. Objective: To assess the accuracy of endoscopic ultrasound (EUS) in the selection of patients with gastric adenocarcinoma for neoadjuvant therapy (T ! 2 and/or Nþ). Methods: Retrospective analysis of patients with an anatomopathological diagnosis of gastric adenocarcinoma between January 2011 and June 2017, who had EUS for staging and underwent surgery as a first therapeutic attempt. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, the pre-operative diagnosis of tumor invasion by conventional endoscopy and/or EUS does not have the same level of diagnostic performance, with a rate of accurate diagnosis of tumor invasion depth ranging between 62–81% for convention endoscopy and 67–85% for EUS 25 28 . Moreover, several studies have reported on the difficulty in performing accurate diagnosis for the lesions in the cardia of the stomach, as well as lesions with ulceration or perifocal inflammatory, and large lesions (> 30 mm) 24 , 29 31 . In our study, 78 lesions (77%) that were diagnosed as M or SM1 cancer were resect by ESD and finally diagnosed as T1b2 carcinoma by pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pre-operative diagnosis of tumor invasion by conventional endoscopy and/or EUS does not have the same level of diagnostic performance, with a rate of accurate diagnosis of tumor invasion depth ranging between 62–81% for convention endoscopy and 67–85% for EUS 25 28 . Moreover, several studies have reported on the difficulty in performing accurate diagnosis for the lesions in the cardia of the stomach, as well as lesions with ulceration or perifocal inflammatory, and large lesions (> 30 mm) 24 , 29 31 . In our study, 78 lesions (77%) that were diagnosed as M or SM1 cancer were resect by ESD and finally diagnosed as T1b2 carcinoma by pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, large, randomised, multi centre trials are warranted for evaluation of new endoscopic techniques and tools in clinical practice. Last but not least, as also highlighted in the present issue of United European Gastroenterology Journal , we should constantly evaluate the efficacy of certain endoscopic procedures in a ‘real life setting’ 8–10 …”
mentioning
confidence: 89%
“…Costa et al [93] found an accuracy of 86% in the selection of patients with gastric adenocarcinoma for neoadjuvant therapy (T2 and/or N+). The sensitivity and specificity were 88.5% and 83.1% with a better performance in the proximal location and intestinal type.…”
Section: Eus In Advanced Gastric Cancermentioning
confidence: 99%